2010
DOI: 10.1007/s00228-010-0815-4
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and risk of significantly raised blood pressure in cancer patients treated with bevacizumab: an updated meta-analysis

Abstract: Among the patients included in the trials analyzed in this meta-analysis, the addition of bevacizumab to cancer therapy treatments significantly increased the risk of significantly raised blood pressure. The risk may be dose-dependent and vary with tumor type.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
46
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(48 citation statements)
references
References 33 publications
1
46
0
1
Order By: Relevance
“…Indeed, several recent meta-analyses have shown that the use of bevacizumab significantly increases the risk of developing anti-VEGF adverse events, including hypertension [5], congestive heart failure (CHF) [6], arterial thrombosis [7], hemorrhage [8,9], proteinuria [10,11] and gastrointestinal perforation [12,13]. Additionally, high-grade infection (Grades 3-4) is a rare but potentially life-threatening adverse event with bevacizumab; this has been observed in clinical trials with an incidence ranging from 0% to 23.2% [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, several recent meta-analyses have shown that the use of bevacizumab significantly increases the risk of developing anti-VEGF adverse events, including hypertension [5], congestive heart failure (CHF) [6], arterial thrombosis [7], hemorrhage [8,9], proteinuria [10,11] and gastrointestinal perforation [12,13]. Additionally, high-grade infection (Grades 3-4) is a rare but potentially life-threatening adverse event with bevacizumab; this has been observed in clinical trials with an incidence ranging from 0% to 23.2% [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…Studies show that the occurrence and the grade of the rash may correlate with the degree of response to therapy and pa ent survival in advanced cancer, with one-year survival being between 2 and 3 mes higher in pa ents that have had rashes and 35% [355][356][357]. It has been repeatedly confirmed that the response rates and the overall survival of the pa ents were significantly higher in pa ents that developed hypertension during treatment, compared with pa ents that did not [358,359]. Polymorphisms in the VEGF gene and the gene coding for the receptor VEGFR2, associated with development of hypertension during treatment with VEGF inhibitors have been recently iden fied [360].…”
Section: Individual Repair Capacity and The Risk Of Toxicity Of An Camentioning
confidence: 91%
“…These authors found a non-significant trend towards a dose-effect relationship, with a risk ratio (RR) of 7.17 (95% CI 3.91-13.13) for a weekly dose of 5 mg/kg compared with a RR of 4.11 (95% CI 2.49-6.78) for a weekly dose of 2.5 mg/kg. The highest RRs were observed under bevacizumab (5 mg/kg/week) for renal cancer (RR 13.77; 95% CI 2.28-83.15) and for breast cancer (RR 18.8; 95% CI 1.23-292.3) [7]. Thus, the increased risk of elevated blood pressure under bevacizumab might be dose-dependent and might vary according to the location of the primitive tumor.…”
Section: Hypertension and Proteinuriamentioning
confidence: 94%
“…Anti-hypertensive treatment was prescribed de novo in about 11-16% of patients. According to a recent meta-analysis assessing 12,949 patients from 19 randomized controlled trials, the overall incidence of elevated blood pressure under bevacizumab reached 8% (6-10%) [7]. Bevacizumab was associated with a significantly increased risk raised blood pressure (RR 5.38; 95% Confidence Interval or CI 3.63-7.97).…”
Section: Hypertension and Proteinuriamentioning
confidence: 98%